2022
DOI: 10.1002/ehf2.14172
|View full text |Cite
|
Sign up to set email alerts
|

What's behind your eosinophilic myocarditis? A case of Churg–Strauss syndrome diagnosed during acute heart failure

Abstract: Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare multisystem disorder; cardiac involvement may include eosinophilic myocarditis. A 67-year-old woman presented with 1-week history of dyspnoea and orthopnoea. She had a history of adult-onset asthma and peripheral eosinophilia. The investigations showed T-wave inversion on lateral leads, peripheral eosinophilia, elevated troponin and BNP values, and severe biventricular systolic dysfunction with diffuse hypokinesia and apical akinesia. Computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Prior to our work, only solitary case reports existed on CMR imaging in histology-proven EM [ 5 16 ]. Recently, Antonopoulos et al [ 24 ] reported CMR findings in a large retrospective cohort of patients with peripheral eosinophilia, but the histologic equivalents of imaging characteristics could not be confirmed as myocardial biopsies were not done.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to our work, only solitary case reports existed on CMR imaging in histology-proven EM [ 5 16 ]. Recently, Antonopoulos et al [ 24 ] reported CMR findings in a large retrospective cohort of patients with peripheral eosinophilia, but the histologic equivalents of imaging characteristics could not be confirmed as myocardial biopsies were not done.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Antonopoulos et al [ 24 ] reported CMR findings in a large retrospective cohort of patients with peripheral eosinophilia, but the histologic equivalents of imaging characteristics could not be confirmed as myocardial biopsies were not done. The earlier case studies [ 5 16 ] showed CMR abnormalities varying by the etiology of EM. Marked subendocardial LGE, with or without intracavitary thrombus, appeared typical for cases of chronic eosinophilia [ 8 10 , 15 ], while more acute cases were often associated with myocardial edema, prolonged values of T1 and T2, and patchy LGE that was predominantly subepicardial [ 5 , 6 , 11 ] but could involve LV subendocardium as well [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation